Comparative study of bone mineral density, calcium, and vitamin D status in the Gujarati and white populations of Leicester. Issue 931 (1st May 2003) - Hamson, C; Goh, L; Sheldon, P; Samanta, A
Abstract : Objectives: To evaluate differences in bone mineral density (BMD), calcium, and vitamin D status between the Gujarati (South Asian) and white populations resident in Leicester and to determine whether this was linked to lifestyle factors. Design: An observational cross sectional study of randomly selected Gujarati and white volunteers aged from 20–40 years. Setting: City of Leicester. Participants: Subjects were randomly selected by age (20–40 years) and ethnicity. A total of 262 individuals volunteered to participate, of which 201 (51 white females, 71 Gujarati females, 37 white males, 42 Gujarati males) were eligible for the study. Main outcome measures: Results of questionnaire, BMD at the hip and lumbar spine, and measurement of serum calcium, albumin, alkaline phosphatase, and 25-hydroxyvitamin D. Results: Male and female white subjects were significantly taller and heavier than their Gujarati counterparts. There was a statistically significant difference in BMD both at the spine (p<0.001) and hip (p<0.001) between the white and Gujarati females with the Gujaratis having a lower BMD. There was a trend for Gujarati males to have a lower BMD at the hip and spine than their white counterparts but these figures did not reach statistical significance. The intensity of cigarette smoking and the amount of alcohol consumption were both higher in the white male and female subjects. Sunlight exposure (>4 hours per day) was significantly higher in white subjects compared with Gujaratis. There were no significant differences in the mean level of serum calcium or alkaline phosphatase between the Gujaratis and whites. A significantly higher proportion (p<0.001) of the Gujarati men and women had a vitamin D level that was not measurable (that is, below the lower limit of the laboratory range of normal). Of those who had a measurable level (that is, in the normal range) mean levels of vitamin D were lower (p<0.05) in the Gujarati men and women. Conclusion: The present study is the first of its kind to note a low BMD in Gujarati subjects of South Asian origin compared with their white counterparts, living in Leicester. This study also confirms the presence of low serum vitamin D levels in Gujaratis. There is a need for more research in South Asians with regard to the collection of normal BMD values. This could provide a more meaningful reference range for identifying South Asians at risk of osteoporotic fractures and may have public health implications of relevance to this ethnic group.